2013
DOI: 10.1007/s00347-013-2937-4
|View full text |Cite
|
Sign up to set email alerts
|

Effektivität antibiotischer Initialtherapie in der Behandlung der kontaktlinsenassoziierten bakteriellen Keratitis

Abstract: Empirical combined regimens remain an effective treatment of contact lens-related keratitis. Fluoroquinolones proved to be inadequate for monotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…The ratio of gram-positive and gram-negative bacteria in our study was similar to geographically and socioeconomically comparable locations, such as Basel (Switzerland), Manchester (UK), New York (USA), and St. Louis (USA) [ 6 , 18 – 20 ]. In line with our results, Steger et al in Basel found a significantly higher ratio of gram-negative bacterial isolates in contact lens samples (71%) than in of conjunctival swabs of patients with bacterial keratitis (37%) [ 16 ]. This association between gram-negative bacterial infection and wearing contact lenses is well known, and possibly caused by biofilm formation [ 21 24 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The ratio of gram-positive and gram-negative bacteria in our study was similar to geographically and socioeconomically comparable locations, such as Basel (Switzerland), Manchester (UK), New York (USA), and St. Louis (USA) [ 6 , 18 – 20 ]. In line with our results, Steger et al in Basel found a significantly higher ratio of gram-negative bacterial isolates in contact lens samples (71%) than in of conjunctival swabs of patients with bacterial keratitis (37%) [ 16 ]. This association between gram-negative bacterial infection and wearing contact lenses is well known, and possibly caused by biofilm formation [ 21 24 ].…”
Section: Discussionsupporting
confidence: 92%
“…In spite of difficulties comparing the bacterial spectrum because of the varying inclusion criteria [ 6 , 10 – 14 , 16 , 17 ], geographic variations in the bacterial spectrum in ocular surface-based isolates have been described [ 5 ]. The ratio of gram-positive and gram-negative bacteria in our study was similar to geographically and socioeconomically comparable locations, such as Basel (Switzerland), Manchester (UK), New York (USA), and St. Louis (USA) [ 6 , 18 – 20 ].…”
Section: Discussionmentioning
confidence: 99%